중국 관광객의 부산음식의 섭취현황 및 만족도에 관한 연구 - 임양이(Yaung-Iee Lim); 이종현(Jong-Hyeon Lee); 김영주(Young-Joo Kim); 정지강(Ji-Kang Jeong); 김신정(Sin-Jeong Kim); 박건영(Kun-Young Park) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2013)
This study was conducted to evaluate the intake of food and degree of satisfaction of services among Chinese tourists in the restaurants in Busan. The choice of what these tourists would eat after touring Busan was also determined. We chose 100 independent Chinese tourists visiting Busan for this study. Students, housewives, highly educated people, and people who visited once or twice were predominant among our study subjects. The Chinese tourists chose the following Busan local foods during their visit: Saengseonhoe (19%), Haemultang (19%), Oribulgogi (17%), Dwaejigukbap (12%), and Dongrae Pajeon (11%). The tourists responded that they would like to eat Bulgogi, Samgyeopsal, Bibimbap, Doenjangjjigae, and Dwaejigalbi again if they revisit Busan, indicating that they prefer general Korean food rather than Busan local food. The degree of satisfaction of Chinese tourists with Busan food was low and their response showed they were not satisfied with the prices and the amount of food served. Services (kindness, cleanliness) in Busan restaurants ranked high in the opinion of Chinese tourists. Of all the courses included in their tour of Busan, shopping for items received the highest score of satisfaction (44%), while food in Busan earned the lowest (10%). As regards intention to revisit Busan, 38% of the Chinese tourists answered yes, and 61% were unsure, and 1% was no. Our survey results indicate that restaurants in Busan city need to prepare food of choice for Chinese tourists and also make an effort to raise satisfaction on the cost and amounts of Busan foods. 부산을 방문한 중국인 관광객은 남자보다 여자가 많았으며, 직업에서는 학생과 직장인이 많았다. 연령은 20대와 30대가 주를 이루었으며, 부산을 방문한 횟수는 1회 또는 2회가 가장 많았다. 관광 중 먹어본 부산의 대표음식으로는 생선회와 해물탕이 각각 19%로 가장 많았으며, 오리불고기, 돼지국밥, 동래파전을 10% 내외로 섭취하였다. 부산을 재방문할 때 먹어 보고 싶은 음식으로는 불고기(19%), 된장찌개(17%), 비빔밥(15%), 돼지갈비(14%), 삼겹살(9%), 김치찌개(6%,) 해물탕(4%), 삼계탕(4%)을 원하였다. 부산음식에 대한 만족도는 후식의 다양성(3.4), 메뉴의 다양성(3.3), 음식의 짜고 매운맛(3.2), 저렴한 음식의 값(3.1), 음식의 양(3.0)의 순서로 만족도를 나타내었다. 음식점의 서비스는 친절도와 청결성에서 4.2의 만족도로 높은 평가를 받았다. 부산의 여행 중 가장 좋았던 점은 44%가 쇼핑을 선택하였고, 음식은 10%로 낮은 값을 나타내었다. 부산을 다시 방문하겠다는 의사는 38%, 잘 모르겠다는 61%를 나타내었다. 본 연구에서 중국인 관광객은 관광지에서의 음식을 중요하게 생각하였고 관광지의 특색 있는 음식을 먹고 싶어 하였으나, 부산음식에 대한 만족도는 다소 낮은 평가를 받았으며 음식의 양과 음식의 가격의 조정이 필요한 것으로 조사되었다. 중국인 관광객은 부산시에서 홍보하고 있는 대표음식보다는 한국의 대표음식을 부산여행 중 먹고 싶어 하였다. 본 연구는 중국인 개별관광객을 대상으로 국한하였으므로 단체관광객과는 차이가 있을 것으로 생각되며, 단체관광객을 대상으로 부산여행 중 음식에 대한 만족도와 그들이 먹고 싶어 하는 메뉴에 대한 추가적인 연구가 필요할 것으로 생각된다.